Moral values representation in the elt textbook endorsed by the government - Amalia, Afifah Nur; Alek, Alek; Hidayat, Didin Nuruddin (SEAN Institute, 2024)
This study depicts moral values in English Language Teaching (ELT) textbooks. This research aimed to examine and articulate the moral principles in English textbooks endorsed by the government. This study used a descriptive-qualitative approach using a content analysis strategy. The researcher used the documentation approach to gather data. The statistics were obtained from English Senior High School textbooks endorsed by the Ministry of National Education. The data were evaluated using the analytical framework developed by Miles et al. (2014), which included three main stages: (a) data condensation, (b) data presentation, and (c) conclusion. The result showed that this book covered all of the eighteen moral values embedded by the Ministry of National Education. Nevertheless, improvement is still needed because the eighteen moral values are distributed unevenly across five units, along with two concluding units.